Study of analytical methods for extracting electric parameters of thin film photovoltaic modules - Perich Ibañez, Renzo Alberto (2020)
In order to find a module’s real efficiency and predict its power and energy production it is necessary to study its behaviour and characterize it in the conditions in which it is installed. The single diode model for photovoltaic (PV) cells relates a cell’s current to its voltage through five electric parameters which give us fundamental information about a module and the physical processes inside its cells. Currently, there are many analytical, numerical and heuristic methods used to extract the model’s parameters, each one with advantages and disadvantages that depend on the technology of the module and climate conditions. Current analytical methods used to extract parameters from silicon modules were applied to thin film PV modules in order to study their validity. This work presents the results of the parameter extraction by comparing the measured current-voltage (IV) curve with the modelled curve, as well as through Normalized Root Mean Square Error (NRMSE) calculations with the objective of comparing and evaluating the selected analytical methods.